Indoor Air Quality Monitoring System for Smart Buildings - Chen, Xuxu; Zheng, Yu; Chen, Yubiao; Jin, Qiwei; Sun, Weiwei; Chang, Eric; Ma, Wei-Ying (Proceedings of the 16th ACM International Conference on Ubiquitous Computing (UbiComp 2014), 2014)
Many developing countries are suffering from air pollution, especially the Particulate Matter with diameter of 2.5 micrometers or less (PM2.5). While quite a few air quality monitoring stations have been built by governments in a city’s public areas, the indoor PM2.5 has not yet been monitored and dealt with effectively. Though many office buildings have a HVAC (heating, ventilation, and air conditioning) system, PM2.5 is not considered as a factor when the system circulates fresh air from outdoors. This paper introduces a real system that we have deployed in the offices of five Microsoft Campuses in China. This system instantly monitors indoor air quality on different floors of a building (including office areas, gyms, garages, and restaurants), enabling Microsoft employees to enquiry the air quality of a place by using a mobile phone or checking a website. The information can guide a user’s decision making, e.g., finding the right time to work out in the gym or turn on individual air filters in her own office. Through analyzing the indoor and outdoor air quality data collected over a long period, our system can even offer actionable and energy-efficient suggestion to HVAC systems, e.g., automatically turning on the system only a few hours earlier than usual if it is a heavily polluted day, or identifying the filters in HVAC system that should be renewed.